2008
DOI: 10.1093/sleep/31.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Electromyographic Activity During REM Sleep in Multiple Muscles in REM Sleep Behavior Disorder

Abstract: Simultaneous recording of the mentalis, flexor digitorum superficialis, and extensor digitorum brevis muscles provided the highest rates of REM sleep phasic EMG activity in subjects with RBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 24 publications
3
113
0
1
Order By: Relevance
“…A similar pattern was seen for PD patients with RBD, who had significantly increased EMG activity in the tibialis muscle during NREM sleep compared to PD patients without RBD. Most studies on RBD have mainly focused on measuring EMG activity during REM sleep, [19][20][21] and to our knowledge no other studies have addressed EMG activity during NREM sleep in patients with iRBD and Parkinson disease. The increase of EMG activity during both REM and NREM sleep may suggest a general instability of mechanisms regulating atonia, although most pronounced during REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was seen for PD patients with RBD, who had significantly increased EMG activity in the tibialis muscle during NREM sleep compared to PD patients without RBD. Most studies on RBD have mainly focused on measuring EMG activity during REM sleep, [19][20][21] and to our knowledge no other studies have addressed EMG activity during NREM sleep in patients with iRBD and Parkinson disease. The increase of EMG activity during both REM and NREM sleep may suggest a general instability of mechanisms regulating atonia, although most pronounced during REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 1 and 2 show examples of phasic and tonic muscular activities, respectively, of the musculus mentalis in REM sleep. The musculus mentalis was selected for EMG measurement because a study showed that it has the highest rate of phasic EMG activity out of a set of 13 simultaneously recorded muscles [10]. The musculus mentalis is also recommended for both phasic and tonic muscular activity evaluation by the AASM [4] and ICSD-2 [8].…”
Section: Algorithmmentioning
confidence: 99%
“…To identify RWA, clinicians monitor the electromyographic (EMG) waveform of the musculus mentalis and/or tibialis anterior during PSG recording, to determine the presence of tonic and/ or phasic muscle activity for each 30-second epoch [9][10][11][12][13]. The scoring manual proposed by the American Academy of Sleep Medicine (AASM) [4] is used as criteria for identifying phasic and tonic muscle activities in REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…measured phasic activity in 3-s epochs in 13 different muscles and Iranzo et al in 5 muscles (mentalis, right and left flexor digitorum superficialis, and right and left extensor digitorum brevis). 25,26 A number of computerized scoring methods have been developed to analyze increased muscle activity in REM sleep. [27][28][29][30] However, the validity of these methods has not yet been tested.…”
Section: Brief Summarymentioning
confidence: 99%
“…39 Recent studies have suggested using EMG recordings from several different muscle groups to increase the sensitivity for detecting RBD. 25 Unfortunately, such recordings were not performed at our institution at the time.…”
Section: 2829mentioning
confidence: 99%